Enhancing Elementary School Student Learning Outcomes through the Use of Mind Mapping Learning Strategies - Isthifa Kemal (Yayasan Zia Salsabila, 2024)
One way to help students become more creative in the learning process is to use the mind mapping method. The purpose of this study was to examine how the mind mapping approach can be used to enhance student learning results. This study falls under the category of qualitative research using a descriptive study design. research that aims to describe and analyze the subject of the study—be it an object, phenomena, event, or issue. Observation, interviews, and documentation methods were used as data gathering methods. Data was gathered for this study, which involved multiple primary school children. the outcomes of the information that researchers gathered from sources, including facts discovered through field observations. Learning leads to a shift in behavior rather than mastery.